The Role of Goblet Cells and Cilia in Respiratory Tract Mucosal Protection: A Literature Study - Ihsan Hakim Haviana (Journal of Innovative and Creativity, 2025)
The human respiratory system relies on a complex defense mechanism to maintain mucosal integrity against foreign particles, pathogens, and environmental pollutants. Among its key components are goblet cells, which produce mucus to trap inhaled contaminants, and cilia, which transport this mucus toward the pharynx for expulsion. This study aims to systematically review the synergistic roles of goblet cells and cilia in respiratory mucosal defense using a Systematic Literature Review (SLR) approach. Data were collected from PubMed, ScienceDirect, Google Scholar, and ResearchGate, focusing on studies published between 2010 and 2025. The findings reveal that effective mucociliary clearance depends on the balance between mucus quality and quantity and the coordinated movement of cilia. Disruptions in this system, whether due to environmental factors such as air pollution and cigarette smoke or infections like influenza and COVID-19, can impair mucus clearance, leading to increased infection risk and exacerbation of chronic respiratory diseases. Furthermore, maintaining the functionality of the mucociliary system is critical for preventing and managing respiratory disorders. Pharmacological interventions, including mucolytics, bronchodilators, and hypertonic saline, as well as the development of molecular therapies targeting mucus regulation, are promising strategies to support mucociliary function. This review emphasizes the importance of understanding goblet cell–cilia synergy in developing effective preventive and therapeutic approaches for respiratory health. Future research should focus on optimizing interventions that preserve mucociliary system function to improve patient outcomes and quality of life in respiratory care.Keywords: First keyword, second keyword, third keyword, forth keyword, fifth keyword